2018
DOI: 10.23736/s1973-9087.18.04949-3
|View full text |Cite
|
Sign up to set email alerts
|

Computerized gait analysis with inertial sensor in the management of idiopathic normal pressure hydrocephalus

Abstract: Identification of a GD pattern for iNPH, especially in rehabilitation, may be useful for recognizing patients who are candidates for surgery, thus avoiding permanent disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…Previous studies have reported that the gait features used in determining the diagnosis of iNPH are not specific for identifying individuals who responded to tap tests ( 17 ). However, some quantitative studies have shown contrary results ( 4 , 18 20 ). Our study provides evidence that gait and balance parameters are useful for quantifying changes after ELD in patients with iNPH.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have reported that the gait features used in determining the diagnosis of iNPH are not specific for identifying individuals who responded to tap tests ( 17 ). However, some quantitative studies have shown contrary results ( 4 , 18 20 ). Our study provides evidence that gait and balance parameters are useful for quantifying changes after ELD in patients with iNPH.…”
Section: Discussionmentioning
confidence: 94%
“…Winter et al ( 22 ) studied changes in the biomechanical walking pattern in healthy elderly individuals and found that double-limb support is a stabilizing factor during a normal gait cycle. Panciani et al ( 18 ) observed a significant reduction in the duration of double support, which was obviously improved after the CSFTT. In the current study, we observed an increased percentage of double support to stabilize inefficient gait control in responders before the ELD, and the duration of double support was improved after the ELD.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, out of 151 patients with suspected hydrocephalus from brain imaging and at least one symptom of the classical triad, 76 were A B C D Fig. 2 Radar plots of the progression of median values of cadence, stride length, total time, total steps, double support, and gait speed for a p-iNPH on TUG, b v-iNPH on TUG, c p-iNPH on 18 mW and d v-iNPH on 18 mW from baseline to T72 h. Distances are normalized with respect to baseline (blue lines) and normative values (green dot lines) derived for TUG from [18,38]; for 18 mW from [33]. Red plots refer to the p-iNPH group, yellow plots to the v-iNPH group.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Stolze et al in a study involving 10 iNPH patients, reported gait speed and stride length as the most responsive parameters in a pre-vs. 24 h post-CSF-TT comparison, whereas cadence and balance remained unaffected [17]. More recently, Panciani et al compared gait performances on 52 iNPH patients pre vs. few hours post-CSF-TT finding improvements in gait speed, stride length and double support duration [18]. Another study compared performances on a timed-up and go test (TUG) pre vs. 24 h post-CSF-TT revealing significant improvements in the sit-to-stand transition, walking time, and the number of steps employed to turn [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation